Геодинамическое развитие Крыма - Дерябин, Н.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The structural evolution of the Crimean peninsula under conditions of the expansion and contraction of Earth's crust at two tectonic stages of the Alpian megacycle [the riftogenous (Mesozoic) and contraction (Cenozoic) ones] is considered.